2015
DOI: 10.1039/c5ra04227e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 2D hydroxyl-rich carbon nitride nanosheets for photocatalytic reduction of CO2

Abstract: Hydroxyl-rich g-C 3 N 4 nanosheets were prepared by ultrasonic exfoliation of bulk g-C 3 N 4 in water. The samples were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, atomic force microscopy, UV-vis absorption spectroscopy, photoluminescence spectroscopy, time-resolved fluorescence decay spectroscopy, Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy and photocurrent response. The results indicated that the bulk g-C 3 N 4 was exfoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 54 publications
(71 reference statements)
3
60
0
2
Order By: Relevance
“…prepared a 2D-hydroxyls rich g-C 3 N 4 (hydroxyl-CN) by employing ultrasonic exfoliation of bulk g-C 3 N 4 (B-CN) [71]. Particularly, the bulk g-C 3 N 4 was exfoliated in H 2 O (strongly polar solvent) to facilitate exfoliation of g-C 3 N 4 .…”
Section: Surface Engineeringmentioning
confidence: 99%
“…prepared a 2D-hydroxyls rich g-C 3 N 4 (hydroxyl-CN) by employing ultrasonic exfoliation of bulk g-C 3 N 4 (B-CN) [71]. Particularly, the bulk g-C 3 N 4 was exfoliated in H 2 O (strongly polar solvent) to facilitate exfoliation of g-C 3 N 4 .…”
Section: Surface Engineeringmentioning
confidence: 99%
“…[54] 3. Nanosheet Photocatalysts for CO 2 Reduction 2D materials are being examined as catalysts for the photoreduction of CO 2 ,a nd these nanomaterials may be classified into two groups:i )metal-containing photocatalysts, such as oxides, [11,39,48,53,54,70,[73][74][75][76][77][78][79][80][81] chalcogenides, [49] bismuth oxyhalides, [82][83][84][85][86][87] layered double hydroxides, [88] and zeolites; [89] ii)metal-free photocatalysts including graphene and its deriv-atives (graphene oxide (GO) and heteroatom-doped graphene), [55,[90][91][92][93][94][95][96] g-C 3 N 4 , [97][98][99][100][101][102] and carbon-doped h-BN. [72] A summary of photocatalytic studies on the reduction of CO 2 with 2D nanosheets is given in Table S1.…”
Section: Confirmation Of Product Formation From Comentioning
confidence: 99%
“…The peak located at 810 cm -1 was assigned to the typical breathing mode of a s-triazine ring, and the peak located at 890 cm -1 may be due to the out-of-plane bending mode of N-H. A bunch of peaks located at the range of 1200-1700 cm -1 were ascribed to the stretching vibration modes of C-N and C=N heterocycles. The broad peak at 3000-3250 cm -1 may have resulted from the N-H stretching vibration of uncondensed amine and hydroxyl groups [7]. It can be found that the intensity of this peak increased when the pH of the solution increased.…”
Section: Resultsmentioning
confidence: 95%